2021
DOI: 10.1177/23993693211045092
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma with malignant pleural effusion: Case report and systematic review of literature

Abstract: Introduction: Renal cell carcinoma metastasizes commonly to visceral organs such as adrenals, liver, lungs, or to bones. Metastases to body cavities such as pleura, pericardium and peritoneum are rare, and almost never in isolation. Case discussion: We discuss here a patient who was diagnosed with renal cell carcinoma following an episode of hematuria and underwent radical nephrectomy for the same. Within a month of surgery, he was evaluated for sudden onset breathlessness and detected to have massive left-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a study conducted in Japan, pleural involvement was found in up to 12% of autopsied patients [ 18 , 19 ]. Pleural involvement in renal cell carcinoma can be explained by the flow of blood from renal veins into the bronchial and intercostal veins via Batson's plexus and through lymphatic spread [ 11 , 19 ]. Metastases from the kidneys spread to the lung parenchyma, mediastinum and pleura in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Japan, pleural involvement was found in up to 12% of autopsied patients [ 18 , 19 ]. Pleural involvement in renal cell carcinoma can be explained by the flow of blood from renal veins into the bronchial and intercostal veins via Batson's plexus and through lymphatic spread [ 11 , 19 ]. Metastases from the kidneys spread to the lung parenchyma, mediastinum and pleura in this manner.…”
Section: Discussionmentioning
confidence: 99%